RSA Encryption & Decryption using JAVA - Ramli, Marliyana (Universiti Teknologi Petronas, 2006)
Encryption refers to algorithmic schemes that encode plain text into non-readable form or cyphertext, providing privacy. The receiver of the encrypted text uses a "key" to decrypt the message, returning it to its original plain text form. The key is the trigger mechanism to the algorithm. Until the advent of the Internet, encryption was rarely used by the public, but was largely a military tool. Today, with online marketing, banking, healthcare and other services, even the average householder is aware of encryption. The implementation of this project will be based on Rapid Application Design Methodology (RAD) and will be more focusing on research and finding, ideas and the implementation of the algorithm, and finally running and testing the algorithm. References and theories to support the research of 'RSA Encryption/Decryption using Java' have been disclosed in Literature Review section. The results of the project are discussed in that particular chapter, followed by the conclusion and recommendations. in